Strategi Promosi dalam Manajemen Pemasaran Pondok Pesantren Al Urwatul Wutsqo Diwek Jombang - Umi Mahfudlotul Khoiriyah; Beny Sintasari (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2019)
Islamic boarding schools as religious education institutions have the main objectives, namely; preparing santri to master the knowledge of Islam (taffaqquh fi al din), then followed by propaganda spreading Islam and the stronghold of the people in the field of morals. Al Urwatul Wutsqo Islamic Boarding School Diwek Jombang includes educational institutions that contribute to the nation by holding promotions to encourage the public to obtain the proper education. The purpose of this study was to determine the promotional strategies in marketing management in the Al Urwatul Wutsqo Islamic Boarding School Diwek Jombang. This type of research is field research. The results of the study indicate that the promotion strategy uses tools; electronic media, stickers, banners, wall clocks, calendars, and personal selling. Marketing management through the stages of planning, organization, actualization, evaluation. The supporting factors are vision, motivation from caregivers, santri whose loyalty and totality and promotional tools are quite interesting. The inhibitors are santri / ustadz who are not visionary and semisi with Islamic boarding schools and some weaknesses of promotional tools. The conclusion of this study is that the implementation of promotional strategies in marketing management of the Al Urwatul Wutsqo Islamic Boarding School Diwek Jombang uses existing management tools and functions in the company's marketing management.